Propriété intellectuelle – Jurisprudence fédérale et cantonale 2007-2011 - Ruedin, Pierre-Emmanuel; Dubois, Julien; Tissot, Nathalie (Bâle: Helbing Lichtenhahn, 2013)
Pierre-Emmanuel Ruedin, Julien Dubois, Nathalie Tissot
Keywords: Pierre-Emmanuel Ruedin; Julien Dubois; Nathalie Tissot